Intraoperative and Postoperative Iron Supplementation in Elective Total Joint Arthroplasty: A Systematic Review. Issue 23 (1st December 2021) - Chaudhry, Yash P.; MacMahon, Aoife; Hasan, Syed A.; Mekkawy, Kevin; Valaik, Daniel; Oni, Julius K.; Sterling, Robert S.; Khanuja, Harpal S.
Abstract : Introduction: Postoperative anemia is associated with substantial morbidity and mortality in total joint arthroplasty (TJA). Our primary objective was to determine whether perioperative iron supplementation improves postoperative hemoglobin levels in TJA. Secondary objectives were to determine the effects of perioperative iron on adverse events, quality of life, and functional measures in TJA. Methods: We conducted a systematic review in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using six databases. We included English-language, randomized controlled trials investigating intraoperative or postoperative iron supplementation in elective TJA that reported postoperative hemoglobin levels in patients aged 18 years or older. Seven eligible studies were identified, among which substantial heterogeneity was noted. Bias risk was low in four studies, unclear in two studies, and high in one study. Three studies assessed oral iron supplementation, three assessed intravenous iron supplementation, and one compared oral and intravenous iron supplementation. All intravenous iron was administered intraoperatively, except in the oral versus intravenous comparison. Results: Postoperative oral iron supplementation had no effect on postoperative hemoglobin levels. Intraoperative and postoperative intravenous iron supplementation was associated with higher postoperative hemoglobin levels and greater increases in hemoglobin levels. Two studies reported rates of anemia and found that intraoperative and postoperative intravenous iron supplementation reduced rates of postoperative anemia at postoperative day 30. No adverse events were associated with iron supplementation. One study found that intravenous iron improved quality of life in TJA patients with severe postoperative anemia compared with those treated with oral iron. Perioperative iron had no effects on functional outcomes. Discussion: We found no evidence that postoperative oral iron supplementation improves hemoglobin levels, quality of life, or functional outcomes in elective TJA patients. However, intraoperative and postoperative intravenous iron supplementation may accelerate recovery of hemoglobin levels in these patients. Level of Evidence: Level I, systematic review of randomized controlled trials